2005
DOI: 10.1111/j.1399-3038.2005.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐binding lectin levels in children with asthma

Abstract: Mannose-binding lectin (mbl), one of the important components of innate immunity, can activate the lectin pathway of the complement system. After binding mannose containing carbohydrate structures of foreign antigen, mbl initiates and regulates the inflammatory responses. Asthma is a complex inflammatory disease of the lung involving many components of the immune system. Our objective was to investigate the serum mbl levels of asthmatic children in comparison with healthy controls. Serum mbl levels were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
3
38
2
Order By: Relevance
“…Earlier studies have reported increased plasma MBL levels and activity in allergic patients [18,19]. High MBL levels in allergic patients also associate with their increased blood eosinophils, which are systemic components of airway inflammation in asthma, and these high levels are sustained even in remission [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have reported increased plasma MBL levels and activity in allergic patients [18,19]. High MBL levels in allergic patients also associate with their increased blood eosinophils, which are systemic components of airway inflammation in asthma, and these high levels are sustained even in remission [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported increased plasma MBL levels and activity in allergic patients [18,19]. High MBL levels in allergic patients also associate with their increased blood eosinophils, which are systemic components of airway inflammation in asthma, and these high levels are sustained even in remission [18,19]. In view of these observations and that of the present study it may be proposed that, in response to an environmental insult, MBL levels may rise in all the individuals, but in those individuals who have elevated plasma MBL levels due inherently to the presence of gene polymorphisms, MBL levels may rise even further and contribute to the increased severity of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have mentioned the important role of MBL on pathophysiological mechanisms of allergies [9][10][11]. Some researchers have defined that MBL concentration of serum was significantly different in allergic patients and healthy people [11][12][13]. In our study of atopic subjects, the mean age was 32.5 and the mean serum level of MBL was 3088.3 ± 669.8 ng/ml.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, elevated serum MBL levels might play a role in inflammatory process through the activation of complement [26]. There are some reports demonstrating elevated plasma MBL levels and complement activity in allergic patients although it has not been clarified whether these results are related with genotypic features or disease pathology [27,28]. However, some studies have suggested that genetically reduced MBL levels increase the susceptibility for COPD and asthma [4,29,30], while some others demonstrated the risk of COPD and asthma in MBL deficient patients were not increased [31,32].…”
Section: Discussionmentioning
confidence: 99%